Immunogenicity of a single-dose compared with a two-dose primary series followed by a booster dose of ten-valent or 13-valent pneumococcal conjugate vaccine in South African children: an open-label, randomised, non-inferiority trial. Issue 12 (December 2020) - Madhi, Shabir A; Mutsaerts, Eleonora AML; Izu, Alane; Boyce, Welekazi; Bhikha, Sutika; Ikulinda, Benit T; Jose, Lisa; Koen, Anthonet; Nana, Amit J; Moultrie, Andrew; Roalfe, Lucy; Hunt, Adam; et al.
Summary: Background: Routine childhood immunisation with pneumococcal conjugate vaccine (PCV) has changed the epidemiology of pneumococcal disease across age groups, providing an opportunity to reconsider PCV dosing schedules. We aimed to evaluate the post-booster dose immunogenicity of ten-valent (PCV10) and 13-valent (PCV13) PCVs between infants randomly assigned to receive a single-dose compared with a two-dose primary series. Methods: We did an open-label, non-inferiority, randomised study in HIV-unexposed infants at a single centre in Soweto, South Africa. Infants were randomly assigned to receive one priming dose of PCV10 or PCV13 at ages 6 weeks (6w + 1 PCV10 and 6w + 1 PCV13 groups) or 14 weeks (14w + 1 PCV10 and 14w + 1 PCV13 groups) or two priming doses of PCV10 or PCV13, one each at ages 6 weeks and 14 weeks (2 + 1 PCV10 and 2 + 1 PCV13 groups); all participants then received a booster dose of PCV10 or PCV13 at 40 weeks of age. The primary endpoint was geometric mean concentrations (GMCs) of serotype-specific IgG 1 month after the booster dose, which was assessed in all participants who received PCV10 or PCV13 as per the assigned randomisation group and for whom laboratory results were available at that timepoint. The 1 + 1 vaccine schedule was considered non-inferior to the 2 + 1 vaccine schedule if the lower bound of the 96% CI for the GMC ratio was greater than 0·5 for at least ten PCV13 serotypes and eight PCV10 serotypes. Safety was a secondary endpoint. This trial is registered with ClinicalTrials.gov (NCT02943902 ) and is ongoing. Findings: Of 1695 children assessed, 600 were enrolled and randomly assigned to one of the six groups between Jan 9 and Sept 20, 2017; 542 were included in the final analysis of the primary endpoint (86–93 per group). For both PCV13 and PCV10, a 1+1 dosing schedule (either beginning at 6 or 14 weeks) was non-inferior to a 2 + 1 schedule. For PCV13, the lower limit of the 96% CI for the ratio of GMCs between the 1 + 1 and 2 + 1 groups was higher than 0·5 for ten serotypes in the 6w+1 group (excluding 6B, 14, and 23F) and 11 serotypes in the 14w + 1 group (excluding 6B and 23F). For PCV10, the lower limit of the 96% CI for the ratio of GMCs was higher than 0·5 for all ten serotypes in the 6w+1 and 14w + 1 groups. 84 serious adverse events were reported in 72 (12%) of 600 participants. 15 occurred within 28 days of vaccination, but none were considered to be related to PCV injection. There were no cases of culture-confirmed invasive pneumococcal disease. Interpretation: The non-inferiority in post-booster immune responses following a single-dose compared with a two-dose primary series of PCV13 or PCV10 indicates the potential for reducing PCV dosing schedules from a 2 + 1 to 1 + 1 series in low-income and middle-income settings with well established PCV immunisation programmes. Funding: The Bill & Melinda Gates Foundation (OPP1 + 152352).